2019
DOI: 10.1101/750042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The molecular anatomy of mouse skin during hair growth and rest

Abstract: HIGHLIGHTS--Comprehensive single--cell transcriptome atlas of full--thickness skin --Outer root sheath (ORS) is composed of two distinct cell types --Companion layer transcriptionally resembles ORS --Transcriptional reconstruction of the internal hair follicle (HF) lineages --Molecular identification of an asymmetric HF--bulb structure --Spatial map of fibroblast subtypes in the skin --Online tool. http://kasperlab.org/tools 2 SUMMARYSkin homeostasis is orchestrated by dozens of cell types that together direct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 61 publications
3
13
0
Order By: Relevance
“…The cellular decrease in DICER throughout mutant HFs was likely due to HF resolve to monoclonality as also shown by the K15PR1Cre+:R26R-Confetti reporter line ( Figure 2H ). Furthermore, the DICER immunostaining pattern in the control animals was consistent with recently available single cell-RNAseq data showing Dicer mRNA expression specifically within a subset of Cx/IRS as well as ORS cells within anagen HFs (Joost S, 2019) ( Figure 2I ), suggesting the cell types of miRNA dependency. Previous findings have underscored the role of miRNAs during skin development and post-natal skin maintenance by manipulating specific cell types.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The cellular decrease in DICER throughout mutant HFs was likely due to HF resolve to monoclonality as also shown by the K15PR1Cre+:R26R-Confetti reporter line ( Figure 2H ). Furthermore, the DICER immunostaining pattern in the control animals was consistent with recently available single cell-RNAseq data showing Dicer mRNA expression specifically within a subset of Cx/IRS as well as ORS cells within anagen HFs (Joost S, 2019) ( Figure 2I ), suggesting the cell types of miRNA dependency. Previous findings have underscored the role of miRNAs during skin development and post-natal skin maintenance by manipulating specific cell types.…”
Section: Resultssupporting
confidence: 88%
“…To test our hypothesis, we performed hair depilation assays during the resting stage of the HF growth cycle (P50) using inducible Tarbp2 and Dicer floxed mouse lines crossed to keratin 15 (K15) PR1Cre transgenic mice ( Figure 1A ). This system dominantly ablates Tarbp2 and Dicer within outer BSCs upon RU486 treatment and not within cycling and basal interfollicular epidermal cells as previously performed (Joost S, 2019, Teta et al, 2012). By visual inspection, both control Tarbp2 +/+ :K15PR1Cre+ and experimental Tarbp2 flox/flox :K15PR1Cre+ mice exhibited hyperpigmentation at 9 days post depilation (DPD) ( Figure 1B ).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Only a few studies have investigated the role of miRNAs during the post-natal period within skin cells. For example, Dicer and Drosha within keratin 5 (K5)-positive epithelial keratinocytes and/or hair follicle medulla and epithelial stem cells (Joost et al, 2020) of young mice were found to be required for post-natal hair follicle growth and plucking-induced anagen development (Teta et al, 2012). Recently, miR-218-5p was shown to regulate post-natal skin and hair follicle development by induction of the Wnt signaling pathway (Zhao et al, 2019), however, the exact cell types involved remain unclear.…”
Section: Introductionmentioning
confidence: 99%